Leisure activities and quality of life among old people in the region of Madrid - Raúl Lardiés-Bosque, Fermina Rojo-Pérez,; Vicente Rodríguez Rodríguez, Gloria Fernández-Mayoralas Fernández; María Eugenia Prieto Flores Karim Ahmed Mohamed; José Manuel Rojo Abuín (Boletín de la Asociación de Geógrafos Españoles)
Resumen